2018
DOI: 10.1016/j.biopha.2018.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Local treatment of the dental caries using nanomaterials

Abstract: Targeted therapy as well as reduced adverse effects are the advantages of local drug delivery in dental caries. The application of nanotechnology in this context has gained increasing momentum during last years. A literature search here has provided a brief overview to present the recent developments in using nanoparticles for local treatment of dental caries. Nanoparticles as delivery systems, can entrap substances/drugs and use the advantages of small size and better penetration. They can also profit from bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 44 publications
0
30
0
Order By: Relevance
“…Research has shown that fluoride has limited ability to remineralize dentin when the residual crystals of the lesion are insufficient [33]. CPP-ACP, which has been consider to promote remineralization of the carious lesions by maintaining a supersaturated state of enamel mineral, plays a key role in the biomineralization of dentin [15,34]. It has also been suggested that CPP-ACP has a multifactorial anticariogenic mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has shown that fluoride has limited ability to remineralize dentin when the residual crystals of the lesion are insufficient [33]. CPP-ACP, which has been consider to promote remineralization of the carious lesions by maintaining a supersaturated state of enamel mineral, plays a key role in the biomineralization of dentin [15,34]. It has also been suggested that CPP-ACP has a multifactorial anticariogenic mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Topographical images of the surface were performed in the tapping mode using a silicon nitride scanning probe in admosphere, in which the probe periodically touches the sample surface, producing higher quality images [15]. Each dentine disk was observed in 4 different sites and obtained three-dimensional images of the dentin surface.…”
Section: Surface Roughness Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Plaque is a form of biofilm created by bacteria such as Streptococcus mutans , Streptococcus sobrinus [ 2 ] and Lactobacilli [ 3 ]. These cariogenic bacteria produce acid (formic-, acetic- and propionic acid) as a by-product during the metabolic process of fermentable carbohydrates, which leads to incipient caries or white spot lesions on tooth enamel [ 4 ], resulting in damaging the enamel, leading to formation of nanoscale pores [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most common anticaries agents (liquids and varnishes) are well accepted by patients, although their retention on the dental surface is poor, leading to limited efficacy [28]. As such, nanometric materials such as nanoparticles with different compositions have been increasingly studied for use as carriers, improving not only their mechanical properties but also modified to achieve the desired size, morphology, and applicability [29,30].…”
Section: Introductionmentioning
confidence: 99%